REFINING POPULATION ESTIMATION AND SURVEY TECHNIQUES FOR WILD TURKEYS - David T. Cobb; John L. Kalso; George W. Tanner (Wildlife Society Bulletin)
Abstract: The ability to monitor population levels with high accuracy, precision, and statistical power at a reasonable cost remains a persistent shortcoming of wild turkey (Meleagris gallopavo) management. Our objectives were to (1) evaluate the maximum likelihood estimate, change‐in‐ratio, mean Peterson, Peterson based‐on‐means, Schnabel, and Buckland models for estimating wild turkey populations; (2) test the applicability of transect techniques for monitoring population trends; and (3) determine the best approach for estimating and monitoring wild turkey populations under conditions in Florida. Significant (P < 0.05) variation in population estimates was found among years, study sites, and estimation techniques. None of the estimators performed well. Among several variables, estimates were most sensitive to variation in percentage of marked turkeys observed during surveys. The Peterson based‐on‐means model was the best estimator of the 6 tested. Survey techniques we tested had sufficient statistical power to detect large (i.e., ≥ 10% annual change), long‐term (i.e., ≥ 10 year) population trends, but were insufficient to detect slight to modest annual changes. We recommend against using traditional mark–resight methods for estimating population size or direct observation surveys for monitoring trends. We recommend further exploration of mark–resight techniques using infrared or remotely activated camera systems to estimate and monitor turkey populations.